Conselho consultivo para pequenas e médias empresas - Borscheid, Neide (2006)
Nowadays, organizations are inserted in a social, technological, political and economical way that demands a great professionalization and the professionals' specialization of who acts in them. The small and median companies, with limited financial resources are obstructed to accomplish many investments in qualified human resources in specific areas, they need a highly qualified administration process, and that reduces, to the maximum, the probability of mistakes as increases the speed of correction of the same ones. This work studies and analyzes the system of management business, of small and median companies, identifying and analyzing the administration actions of a median company. The bibliographical research presents the analysis of the subjects that involve the administration of small and median companies, corporative management and council administration, emphasizing the approaches to present solutions for the research problem. The present work has as mark to propose an Advisory Council model, for small and median companies, directed to help the managers, of those organizations find an efficient and effective form of all of the available resources, presenting a business model directed to the reality and need of the same ones. This work methodology refers to a research of qualitative nature that we used for the development of its process, the research-action technique.